2001
DOI: 10.1099/0022-1317-82-10-2437
|View full text |Cite
|
Sign up to set email alerts
|

Generation of infectious and transmissible virions from a GB virus B full-length consensus clone in tamarins

Abstract: The strong similarity between GB virus B (GBV-B) and hepatitis C virus (HCV) makes tamarins infected by GBV-B an acceptable surrogate animal model for HCV infection. Even more attractive, for drug discovery purposes, is the idea of constructing chimeric viruses by inserting HCV genes of interest into a GBV-B genome frame. To accomplish this, infectious cDNA clones of both viruses must be available. The characterization of several HCV molecular clones capable of infecting chimpanzees has been published, whereas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
27
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 41 publications
(55 reference statements)
4
27
0
Order By: Relevance
“…4C). These titers are comparable with those obtained for the wild-type infectious GBV-B clone, which gave values ranging from 1-3 ϫ 10 9 ge/ml for data collected from four tamarins (15,17). 4 At weeks 6, 12, 14, and 16 post-inoculation, the genomic sequence was determined from viral RNA isolated from serum.…”
Section: Maturation Of Core By Spp Is Essential For Productive Gbv-b supporting
confidence: 67%
See 1 more Smart Citation
“…4C). These titers are comparable with those obtained for the wild-type infectious GBV-B clone, which gave values ranging from 1-3 ϫ 10 9 ge/ml for data collected from four tamarins (15,17). 4 At weeks 6, 12, 14, and 16 post-inoculation, the genomic sequence was determined from viral RNA isolated from serum.…”
Section: Maturation Of Core By Spp Is Essential For Productive Gbv-b supporting
confidence: 67%
“…GB virus B (GBV-B) can act as a surrogate model of HCV infection, because the two viruses have identical genome organizations and share significant sequence similarity (12)(13)(14)(15)(16)(17)(18)(19). GBV-B establishes an acute infection in several species of New World monkeys including tamarins (Saguinus sp.)…”
mentioning
confidence: 99%
“…Another possibility is that the transmission mode influences the outcome, since both animals were transfected from molecular clones. However, five animals that we transfected with the wild-type clone all had acute resolving infections, as did two animals transfected with another molecular GBV-B clone (21). Lanford et al (13) observed that transient immunosuppression of four tamarins could prolong GBV-B viremia in some cases, but it did not lead to persistent infections.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to HCV infection, which frequently progresses to chronicity in humans and in experimentally infected chimpanzees (9), all reported GBV-B infections in tamarins initiated with wild-type virus have resolved during the acute phase (1,3,4,21,23). Recently, however, it was reported that an animal transfected with RNA transcripts from a full-length GBV-B clone had viremia for more than 2 years before it cleared the infection (15).…”
mentioning
confidence: 99%
“…Upon intrahepatic inoculation of tamarins (Saguinus spp. ), only genomes with the complete 3Ј NTR were viable, showing that this region is essential for infectivity (8,51). For pestivirus BVDV, it was shown that mutations within the 3Ј- 3 and 22 to 24).…”
Section: Vol 76 2002mentioning
confidence: 99%